(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Azithromycin is a widely used broad-spectrum antibiotic that was recently used in the treatment protocol of COVID-19 but its cardiac side effects became a more prominent concern. Rosuvastatin is a synthetic statin that showed anti-inflammatory, antioxidant and autonomic nervous system regulatory effects in addition, there is increasing evidence supporting that it could play a beneficial role in patients with COVID-19. Objective To evaluate the protective effect of Rousvastatin against Azithromycin-induced cardiotoxicity in Covid-19 patients. Patients and Methods This is a prospective study that was conducted on adult patients diagnosed with COVID-19 who were admitted to isolation centres in Minia Governorate, Egypt for the period of one year (June 2021 to May 2022). The study included a total of 80 COVID-19 patients who were divided into 2 groups (n=40 each), group (I) "Azithromycin group" that included patients received Azithromycin (500 mg/day for 5 days) orally and group (II) "Azithromycin + Rosuvastatin group" that included patients received Azithromycin by oral route as group (I) plus Rosuvastatin 20 mg/day orally. All included cases were subjected to full history taking, clinical examination and laboratory investigations and after treatment, the outcome measures were reported and compared. Results No significant differences were observed between groups regarding demographic and baseline characteristics. Also, the two groups were comparable with no significant differences in pulse rate, blood sugar, CBC, electrolyte elements, liver enzymes, and kidney function (a slight reduction was noticed in group II). While, Ferritin level was significantly lower in group (II) compared to group (I), (830 ± 72.5 vs. 865 ± 69.5, p=0.03). No significant differences were observed among groups as regards Troponin level (p=0.56) "Only one case was positive in group (I)". Both groups were almost comparable without significant differences in both stages of infection and mortality (p=0.38 and 1.0, respectively). Conclusion Rosuvastatin did not have a significant role in the protection of Azithromycin-induced cardiotoxicity, it slightly ameliorates the biochemical and stress markers alterations of Azithromycin. Further larger studies are warranted for investigating this issue.